New Benzophenones and Xanthones from Cratoxylum sumatranum ssp. neriifolium and Their Antibacterial and Antioxidant Activities - Cholpisut Tantapakul (2018)
© 2016 American Chemical Society. Two new benzophenones (1 and 2) and four new xanthones (4-6 and 17) together with 24 known compounds (3, 7-16, and 18-30) were isolated from the roots and twigs of Cratoxylum sumatranum ssp. neriifolium. Their structures were elucidated by spectroscopic methods. Compounds 5 and 26 showed antibacterial activity against Micrococcus luteus, Bacillus cereus, and Staphylococcus epidermis with minimum inhibitory concentrations ranging from 4 to 8 μg/mL, whereas compounds 7, 20, and 26 displayed selective antibacterial activities against Staphylococcus aureus (8 μg/mL), Salmonella typhimurium (4 μg/mL), and Pseudomonas aeruginosa (4 μg/mL), respectively. The radical scavenging effects of some isolated compounds were investigated. Compounds 11 and 21 exhibited potent activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) with IC50values of 7.0 ± 1.0 and 6.0 ± 0.2 μM, respectively.